Osmo-Convective Dehydration of Cauliflower - Manjunatha, M; Garg, M K; Wadhwa, J M (Journal of Agricultural Engineering, 2007)
The blanched cauliflowers were soaked in sucrose solution of varying concentrations (15, 25, 35degree Brix) at different temperatures (ambient temperature, 40degree C and 50degree C) for 30 min. This was followed by treatment with mixture of common salt (10%) + potassium metabisulphite (0.5%) for 15 min at 30degree C. Samples were further dried under convective drying method at 60degree C and it took 8 h to achieve final moisture content for safe storage. Osmo-convective dried cauliflower packed in low-density polyethylene bags (LDPE, 50 um) were kept for storage studies. The water loss, convective drying behaviour and ascorbic acid retention were determined during experiment. During osmosis, water loss ranged from 14.9 to 30.8%. The loss of ascorbic acid during blanching and osmotic dehydration was found 30.6% and 30 to 36.4%, respectively. The loss of ascorbic acid ranged from 11.8-26%, 18.0-41.6% and 20.6-51.7% in the first, second and third month of storage.